Mycelial cultivation of Phlebopus spongiosus, an edible ectomycorrhizal mushroom in Southern Vietnam - Le Thi Thuy Nhi; Tran Chi Hieu; Phan My Hanh; Bui Van Tan; Pham Nguyen Duc Hoang; Ho Bao Thuy Quyen (Ho Chi Minh City Open University Journal of Science - Engineering and Technology, 2017)
Phlebopus spongiosus is an endemic edible ectomycorrhizal mushroom (EEMM) in Southern Vietnam. Strains of Phlebopus spongiosus – collected from Pomelo orchards, Ben Tre Province, Vietnam – were cultured on different media, temperatures, pH and carbon/nitrogen sources to define mycelial growth conditions for spawn mushroom production. Phlebopus spongiosus BC-F0075 grew the fastest on the modified MS medium. The optimum temperature for mycelial growth was 30°C and the optimum pH was 4 – 5. BC-F0075 grew well on the MS media containing saccharose, glucose, fructose and maltose, but did not with lactose. Additionally, NH4H2PO4 was reported to be the best nitrogen source to the growth of BC-F0075 mycelia, whereas urea ((NH2)2CO) was not utilized as a nitrogen source.